Ways of European Historiography to the Diplomacy of Early Modern Period (Theatrum historiae, 2013)
While positivist science of the 19th century perceived the history of diplomacy as the history of impersonal state formations, the 20th century began, behind international treaties and complicated negotiations, to see persons of individual diplomats and their closest surroundings. Therefore historiography, under the influence of cultural anthropology, strives to approach to the history of diplomacy as a cultural phenomenon. This article tries to describe that demanding way and paradigm change when exploring the history of diplomacy in early modern period, both in (western) European space and the Czech historiography, which started to accept new impulses just after 1990.
Keywords: history of historiography; history of diplomacy; nobility; early modern period